The Shipwreck's spectator form an anthropological point of view (2014)
The hermeneutic applicability of the metaphors-set implied in the paradigmatic «Shipwreck with Spectator» goes beyond the understanding of the non-conceptual background of theoretical attitude towards existence. The seafaring metaphor can be also used to explain the borderline between Secured Lands and Risk Spaces, inviting us to recognize the oscillating of any anthropological surviving work, implied in the existential praxis of contemplating any storm; not only the epic attitude of temerarious heroes who look inside the abysm, standing in their boundaries. The shore from we «watch» the show of the shipwreck is no more the Terra Firma that used to be. The sinking then becomes an opaque referent of the long detour of life that we do in order to dilate the crude face-to-face with the darkest sea's deeps. © PENSAMIENTO.